Green tourism during the COVID-19 pandemic: health protocol moderation analysis - Asep Rokhyadi Permana Saputra; Dani Iswara; Mohamed Nor Azhari Azman; Hafizah Hajimia (Intelektual Pustaka Media Utama, 2022)
The growth rate of green tourism/ecotourism in the province of Yogyakarta, Indonesia decreased drastically because of the government's program in the community activity restriction program to reduce the COVID-19 pandemic. The purpose of this study was to analyze public perceptions of ecotourism conditions during the pandemic by implementing health protocols and maintaining environmental sustainability. The research employed descriptive and quantitative analysis. The research subject was 222 beach ecotourism tourists in the Special Region of Yogyakarta, Indonesia during the pandemic period for a period of seven months (February-August 2021). They were recruited through incidental random sampling method. The analytical tools in testing the research instrument were convergent validity test with mean loading factors and square roots average variable extract, discriminant validity test with average variable extract (AVE), and reliability test with Cronbah's alpha and composite reliability (CR), structural equation modeling analysis (SEM) with Warp partial least square (PLS) 7.0. The results showed that ecotourism concern, ecotourism practices, were not significant on tourist satisfaction. Green promotion had an effect on ecotourism tourist satisfaction, and health protocols strengthened tourist satisfaction on tourists' interest in returning to ecotourism.